Warding off evil : an analysis of apotropaic tradition in the Dead Sea Scrolls and Synoptic Gospels - Morris, Michael (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2016)
This thesis is comprised of five chapters which address human responses to personified evil in the Dead Sea Scrolls and the synoptic gospels. One response, exorcism, is prevalent in each of the synoptics and has been given substantial scholarly attention. It is clear from these studies that demonological beliefs in early Judaism influenced New Testament literature, and there are numerous parallels between early Jewish and synoptic portrayals of exorcism. However, "apotropaism," which is a preventative measure that wards off demonic beings before affliction can take place, is also present in early Judaism, yet has been given only minor consideration in scholarly discussions of the synoptic tradition. This study offers an in-depth examination of apotropaic tradition in order to fill a void and advance critical assessments of the depiction of human interaction with personified evil in the gospels.
Keywords: Religions, Peace Studies & Theology, Ph.D.; PhD Trinity College Dublin, 2016